The role of interaction between keratinocytes and type 2 inflammation in the pathogenesis of atopic dermatitis - Ruiwen ZHANG; Xiaobao HUANG; Fang WANG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2024)
Patients with atopic dermatitis (AD) have skin barrier dysfunction, which is closely related to keratinocyte (KC) abnormalities. Upon stimulation by external factors, KCs release a large number of inflammatory mediators, thereby activating type 2 inflammation, which, in turn, exacerbates skin barrier dysfunction. Thus, the interaction between KCs and type 2 inflammation is a key factor in the pathogenesis of AD, and exacerbation of inflammation and pruritus. At present, the innovative medications, such as biologics and small molecule drugs, have been shown anti-inflammatory effects in AD. Studies also demonstrate their role in skin barrier repair. Therefore, research on the interaction between KCs and type 2 inflammation will help understand the pathogenesis of AD and provide evidence to optimize treatment strategies for AD.